Analisis Uji Peluncuran Roket Air Berbasis Carbon Fiber Menggunakan Sistem Telemetri - Qonitatul Hidayah; Umi Salamah; Margi Sasono (Department of Physics, Faculty of Mathematics and Natural Sciences, University of Lampung, 2022)
Rocket technology with water propellant is becoming more popular and as an alternative to be applied to education and recreation, such as industry and the military. The use of water rockets as an easy, safe, and inexpensive means of measuring physical parameters at heights above the earth's surface is being intensively carried out. One alternative solution is aerodynamic water rocket technology equipped with a telemetry system. The rocket used for the test launch is made from untested carbon fiber. Flight test settings by filling 1/3 of the tube volume with water and a pressure of 200 psi. The results of the water rocket launch show a maximum height of 265 feet or 80.77 m. Changes in acceleration on the x-axis, y-axis, and z-axis indicate the normal motion of the flying rocket. Analysis of stability and control of the rocket is seen in the measurement of the tilt angle of roll, pitch, and yaw. When the rocket moves or tilts, the angle measured corresponds to the tilt. In the roll condition, the rocket moving from launch to landing shows the rocket's rotational motion at an angle of approximately 20o. The potential of water rockets that can still be developed, needs to be increased the reliability of water rockets both in terms of utilization and research.